Optimizing Hyperledger dApp Efficiency: Gas Consumption in Hardhat and Truffle Frameworks - M. Shakila (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Blockchain technology has completely changed how decentralised applications (dApps) operate by improving security, transparency, and efficiency to previously unheard-of levels. It is imperative that the use of specialized tools result in the effective creation of the frameworks and tools used in this process. The crucial measures that are part of the computational effort and operations that go into developing the development of enhanced immutability. Ether payments, which stand for the transaction fees associated with each transaction, are necessary for the smart contract to be executed. This research explores the use of blockchain technology in voting to improve security, increase transparency, and deal with problems like manipulation and fraud. The usefulness of the Hardhat and Truffle frameworks is examined. An execution is conducted on the utility of Hardhat and Truffle frameworks for smart contract development, supporting developers in achieving cost-efficiency by embedding gas estimation and customizable gas configuration within the system. This analysis aims to provide a thorough assessment of gas consumption as compared to transactions using Ethereum Truffle, with the goal of identifying the most efficient framework for smart contract deployment. The primary objective is to compare gas usage metrics in evaluating these frameworks. The methodology entails deploying identical gas consumption measurements to assess the cost-effectiveness of implementing Blockchain-based systems. This involves evaluating gas consumption across various transaction scenarios to optimize ether usage. Consequently, data is securely stored and accessed by applications through frontend interfaces and Ethereum nodes, ensuring the immutability of systems. Collaboration between frontend and backend components is crucial in developing user-friendly and secure systems. In Future ,we present a framework for conducting optimization experiments in a distributed setting and for storing both the environmental result data and environmental studies. This framework facilitates not only the organized implementation of experiments but also the potential reuse of outcomes in subsequent endeavors.